1996
DOI: 10.1152/jappl.1996.81.5.1891
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fatigue and exhaustion during dynamic leg exercise in normoxia and hypobaric hypoxia

Abstract: Using an exercise device that integrates maximal voluntary static contraction (MVC) of knee extensor muscles with dynamic knee extension, we compared progressive muscle fatigue, i.e., rate of decline in force-generating capacity, in normoxia (758 Torr) and hypobaric hypoxia (464 Torr). Eight healthy men performed exhaustive constant work rate knee extension (21 +/- 3 W, 79 +/- 2 and 87 +/- 2% of 1-leg knee extension O2 peak uptake for normoxia and hypobaria, respectively) from knee angles of 90-150 degrees at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 35 publications
(38 reference statements)
9
82
2
1
Order By: Relevance
“…During MVC without fatigue, acute hypoxia has no effect on maximal EMG, in accordance with unchanged maximal voluntary strength (83). When comparing the evolution of maximal iEMG during MVC after submaximal contractions at the same absolute intensity, similar [after 3 sets of isometric leg extensions (54) and after 10 min of cycling (106)] or greater [after dynamic leg extensions to exhaustion (35)] reductions in MVC iEMG have been reported in hypoxia compared with normoxia. A greater reduction in MVC iEMG may reflect some alterations in central neural pathways, partly explaining the greater reduction in MVC observed under hypoxic conditions (35).…”
Section: Central Motor Commandmentioning
confidence: 71%
See 1 more Smart Citation
“…During MVC without fatigue, acute hypoxia has no effect on maximal EMG, in accordance with unchanged maximal voluntary strength (83). When comparing the evolution of maximal iEMG during MVC after submaximal contractions at the same absolute intensity, similar [after 3 sets of isometric leg extensions (54) and after 10 min of cycling (106)] or greater [after dynamic leg extensions to exhaustion (35)] reductions in MVC iEMG have been reported in hypoxia compared with normoxia. A greater reduction in MVC iEMG may reflect some alterations in central neural pathways, partly explaining the greater reduction in MVC observed under hypoxic conditions (35).…”
Section: Central Motor Commandmentioning
confidence: 71%
“…During intermittent submaximal contractions of the knee extensors, Fulco et al (35) and Katayama et al (54) showed that acute hypoxia (PI O 2 ϭ 464 Torr and FI O 2 ϭ 0.11, respectively) accelerates the increase in iEMG from the beginning to the end of exercise. This increase in iEMG is interpreted as an increase in motor command to recruit additional motor units and/or to increase motoneuron discharge rate to compensate for contractile failure in active muscle fibers.…”
Section: Central Motor Commandmentioning
confidence: 99%
“…It may also result from progressive cold penetration through the muscle tissue (Oksa et al 2002) gradually increasing the number of muscle fibres affected by slowed intramuscular energetics (Bergh, 1980;Faulkner et al 1990;De Ruiter & De Haan 2000;Allen et al 2008;Racinais & Oksa, 2010;Cahill et al 2011). Conversely, the mild effect of hypoxia on mechanical function (fatigue) has been widely attributed to increases in energetic metabolite interference with Ca 2+ handling and the contractile proteins (Edwards 1981;Fulco et al 1996;Fitts 1994;Haseler et al 1999;Hogan et al 1999;Amann & Calbet 2007;Perrey & Rupp 2009;Christian et al, 2014a).…”
Section: Mechanical Fatigue In Hypoxic-coldmentioning
confidence: 99%
“…However, increases in muscle fatigue during prolonged exercise in hypoxia have been observed during both whole-body (Amann & Calbet 2007) and repeated contractions of isolated muscle groups (Fulco 1994;Katayama et al 2007;Perrey & Rupp 2009;Millet et al 2008;Christian et al 2014a). The rise in muscle fatigue during hypoxia can be largely attributed to a shift of the relative exercise intensity, higher muscle fibre recruitment, and thereby increased intramuscular metabolic disturbance (Edwards 1981;Fulco et al 1996;Amann et al 2006a;2006b;2007a;2007b;Fulco et al 1994, Katayama et al 2007Christian et al 2014a). Specifically, the increase in inorganic phosphate, reactive oxygen species and hydrogen ion production and their interference with the contractile proteins and sarcoplasmic Ca 2+ release mechanisms are thought to be a major factor behind the increase in muscle fatigue development Hogan et al 1999;Amann & Calbet 2007;Perrey & Rupp 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation